Codon Usage Bias and Cluster Analysis of the MMP-2 and MMP-9 Genes in Seven Mammals - Tanliang Ouyang; Jincheng Zhong; Zhixin Chai; Jiabo Wang; Ming Zhang; Zhijuan Wu; Jinwei Xin (Genetics Research)
Matrix metalloproteinase (MMP)-2 and MMP-9 are a family of Zn2+ and Ca2+-dependent gelatinase MMPs that regulate muscle development and disease treatment, and they are highly conservative during biological evolution. Despite increasing knowledge of MMP genes, their evolutionary mechanism for functional adaption remains unclear. Moreover, analysis of codon usage bias (CUB) is reliable to understand evolutionary associations. However, the distribution of CUB of MMP-2 and MMP-9 genes in mammals has not been revealed clearly. Multiple analytical software was used to study the genetic evolution, phylogeny, and codon usage pattern of these two genes in seven species of mammals. Results showed that the MMP-2 and MMP-9 genes have CUB. By comparing the content of synonymous codon bases amongst seven mammals, we found that MMP-2 and MMP-9 were low-expression genes in mammals with high codon conservation, and their third codon preferred the G/C base. RSCU analysis revealed that these two genes preferred codons encoding delicious amino acids. Analysing what factors influence CUB showed that the third base distributors of these two genes were C/A and C/T, and GC3S had a wide distribution range on the ENC plot reference curve under no selection or mutational pressure. Thus, mutational pressure is an important factor in CUB. This study revealed the usage characteristics of the MMP-2 and MMP-9 gene codons in different mammals and provided basic data for further study towards enhancing meat flavour, treating muscle disease, and optimizing codons.